If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -2) + -1(x + 6) = 4(x + -1) Reorder the terms: 3(-2 + x) + -1(x + 6) = 4(x + -1) (-2 * 3 + x * 3) + -1(x + 6) = 4(x + -1) (-6 + 3x) + -1(x + 6) = 4(x + -1) Reorder the terms: -6 + 3x + -1(6 + x) = 4(x + -1) -6 + 3x + (6 * -1 + x * -1) = 4(x + -1) -6 + 3x + (-6 + -1x) = 4(x + -1) Reorder the terms: -6 + -6 + 3x + -1x = 4(x + -1) Combine like terms: -6 + -6 = -12 -12 + 3x + -1x = 4(x + -1) Combine like terms: 3x + -1x = 2x -12 + 2x = 4(x + -1) Reorder the terms: -12 + 2x = 4(-1 + x) -12 + 2x = (-1 * 4 + x * 4) -12 + 2x = (-4 + 4x) Solving -12 + 2x = -4 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -12 + 2x + -4x = -4 + 4x + -4x Combine like terms: 2x + -4x = -2x -12 + -2x = -4 + 4x + -4x Combine like terms: 4x + -4x = 0 -12 + -2x = -4 + 0 -12 + -2x = -4 Add '12' to each side of the equation. -12 + 12 + -2x = -4 + 12 Combine like terms: -12 + 12 = 0 0 + -2x = -4 + 12 -2x = -4 + 12 Combine like terms: -4 + 12 = 8 -2x = 8 Divide each side by '-2'. x = -4 Simplifying x = -4
| (2(x^2)+2)= | | (4y)(4y)= | | (M^0)(-4)= | | 3+2(x-7)=x-18 | | 24a^4-4a^4= | | -(u-w)-6(-3w-6u)= | | 6x^6-60x^5-144x^4= | | 45x-5=546 | | 6(3z-1)-5(z+5)=10(z+1) | | 5(z-4)+4z=5-6z | | 3x^2-25x+36=0 | | O(9)=2(9)-1 | | x^2=-112 | | 7-2y=11-6y+4y | | 2x+5y=-2 | | 3x+4+x-10=2+x-4 | | -22=4x | | 12y-5y=39+4y | | 2x+4+8x-1=18 | | 0=4x^3+.808x^2-.000000000185 | | 4x-1.3=8.7 | | (5/3)x=-70 | | 4a-9=3(a-3) | | 2x+23=4(x+5) | | 4a-9=3(a-9) | | x+2.3=4.1 | | (6x-5)/4=3 | | 3r+6=48+11r | | 5c-6=-9 | | 12-8-3= | | 12x+4=3(4-2) | | 3(7x-6)=5(2+5x) |